Volume 1 2004
DOI: 10.1115/ht-fed2004-56672
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Convection in Tilted Cylindrical Cavities Embedded in Rocks

Abstract: We present a theoretical and experimental study of the thermal convection in a fluid-filled, tilted cylindrical cavity and in a fluid-saturated porous medium filling a cylindrical cavity embedded in a solid slab (solid rock) which has a constant vertical temperature gradient far from the cavity. Closed-form, analytical solutions are obtained for the temperature field in the solid and for the velocity, temperature and pressure within the cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Spots were visualised by 0.1% Rhodamine B and scrapped and used for fatty acid analysis. The amount of fatty acid ingested was calculated on the basis of percentage in the fat (Sa´nchez-Muniz et al, 1992b) and the proportion of fat in the diet.…”
Section: Lipid Fractionsmentioning
confidence: 99%
“…Spots were visualised by 0.1% Rhodamine B and scrapped and used for fatty acid analysis. The amount of fatty acid ingested was calculated on the basis of percentage in the fat (Sa´nchez-Muniz et al, 1992b) and the proportion of fat in the diet.…”
Section: Lipid Fractionsmentioning
confidence: 99%
“…This effect cannot be attributed to the different saturated, monounsaturated or polyunsaturated nature of the diets (Ganji and Kies, 1993) nor to the decreased palatability due to marine lipid oxidation (Herman et al, 1991). In fact, the group that consumed fried sardine oil, in which oxidation was necessarily greater due to the frying procedure (Sa´nchez-Muniz et al, 1992), actually displayed a higher food intake than the group that consumed olive oil ( Table 2). The oils from raw and fried sardines were treated with the addition of BHT and BHA to prevent oxidation during the extraction process.…”
Section: Resultsmentioning
confidence: 96%
“…Information concerning the influence of raw fats on the utilisation of minerals exists (Kaup et al, 1990), but it is less known about the effects of the intake of fats which have undergone cooking procedures, such as frying, on mineral utilisation (Pe´rez-Granados et al, 1993, 1999, 2000a,b, 2001a. In the frying process, an exchange occurs between the oil used and the fat of the food being fried (Sa´nchez-Muniz et al, 1992). With regard to the polyunsaturated fats from fish, our working group found that a diet rich in raw sardine oil produced metabolic alterations of iron, including a depletion of this element (Pe´rez-Granados et al, 1995) as well as modifications in the bioavailability of calcium and phosphorus (Pe´rez-Granados et al, 2000c).…”
Section: Introductionmentioning
confidence: 99%